Is nature our relative? What is the relationship between the Sámi people and nature and how do they deal with this relationship? - Henriksen, Jan Erik (Sámi dieđalaš áigečála, 2024)
One feature of Indigenous peoples is their close connection to nature. Sustainable use of nature or meahcci (in the Sámi language) is a central part of the way of life and cultural practice of the Sámi People. In this article, I look at five different ways to deal with nature. Firstly, an antropocentric way in which we see human beings as superior to nature. Another way involves coping with nature or birgehallat because we have survival skills and know how to read and interpret the signs of nature and the weather. As an alternative, can we talk about our relationship with nature as gulahallan (communication) or lonohallan (transaction), in other words a kind of exchange? Or are the relationships so close that they can be understood as a kind of kinship? Relationships need to be maintained if they are to last. How do elderly Sámi cope with these relationships? And what happens as people age and health challenges emerge? This study is based on a photovoice method in which 12 homebound North Sámi-speaking elderly people have photographed and created photovoices about nature.
Keywords: survival skills; nature; kinship; relationship; communication; transaction; ageing; anthropocenterism; photovoice method